Thin bandwidth knowledge of results (KR) improves performance consistency on motor skill acquisition - Miguel Junqueira, A. H.; Novellino Benda, R.; Peixoto dos Santos, S.; Menezes Lage, G.; Vieira, M. M.; Pinto Carvalho, M. F. S.; Ugrinowitsch, H. (American Journal of Sports Science, 2015)
The bandwidth knowledge of results in one way of supplying feedback during practice, which provides control over the amount and type of information given to the subject. The present study investigated the best distribution of this information throughout the practice. A task requiring to perform a sequence of movements on the keypad, in order to achieve a specific the target time. The experiment consisted of three stages: a) acquisition (50 attempts); b) transfer, ten minutes after the end of the acquisition (10 attempts); c) retention, twenty-four hours after the end of the acquisition (10 attempts). Participants were distributed into four groups: wide bandwidth, with a range of 20%; narrow bandwidth, with a range of 5%; increasing bandwidth with a range of 5% on the first half of the acquisition and 20% on the second half; and decreasing bandwidth, with a range of 20% on the first half and 5% on the second one. The results show thin bandwidth improves performance consistency.